PROGRAM KOMPUTER SAWUT (SISTEM AKUTANSI WAKAF UANG TUNAI) SEBAGAI HAK CIPTA ( STUDI OBJEK WAKAF PADA BADAN WAKAF INDONESIA ) - Nabila Ramadhani (2023)
Waqf is a legal act of a person (wakif) who surrenders part or all of the waqf object that is in the hands of the wakif with the aim of donating the benefits of the waqf object for the public interest. Copyright can be used as an object of waqf as regulated in Article 16 paragraph (3) letter (e) of Law Number 41 of 2004 about Waqf. The SAWUT computer program (Cash Waqf Accounting System) with Copyright as Intellectual Property Rights that is donated to the Indonesian Waqf Board is a movable property that contains value and does not run out when consumed, so that it fulfills the waqf requirements. This research aims to find out what are the factors that cause the SAWUT Computer Program (Cash Waqf Accounting System) as waqf property and how the transition of the SAWUT Computer Program (Cash Waqf Accounting System) as a copyright becomes a waqf object at the Indonesian Waqf Board. This research is a normative research conducted by examining the laws and regulations related to waqf and copyright and is supported by looking at a legal reality in society. The legal material used are primary, secondary and tertiary legal materials. The problem approach used are statue approach and conceptual approach using normative analysis supported by legal opinions from related parties. The results of the research show that the SAWUT Computer Program (Cash Waqf Accounting System) as a copyright fulfills the requirements of waqf assets that have been regulated in the Waqf regulations. As for the transfer of waqf to the SAWUT Computer Program (Cash Waqf Accounting System), there was no participation of Deed of Waqf Pledge Making Officer so that the waqf did not have a Deed of Waqf Pledge to guarantee legal certainty for the parties.